Kinematics and Aerodynamics of Dragonflies (Pantala flavescens, Libellulidae) in Climbing Flight - Peng, Liansong; Pan, Tianyu; Zheng, Mengzong; Song, Shiying; Su, Guanting; Li, Qiushi (Frontiers in Bioengineering and Biotechnology, 2022)
This study presents a detailed analysis of dragonflies during climbing by integrating high-speed photogrammetry, 3D reconstruction, and computational fluid dynamics. In this paper, the climbing of dragonflies is captured by two high-speed cameras with orthogonal axes. By feature points matching and 3D reconstruction, both body kinematics and wings kinematics of 22 dragonflies in climbing flight are accurately captured. The experiment results show that the climbing angles η are concentrated in two ranges, 60°~70° and 20°~30°, which are defined as large angle climb (LAC) and small angle climb (SAC) respectively. During the climbing process, when the η is similar, it is found that the kinematic parameters of dragonfly's body and wings are basically unchanged. With the increase of η, the phase difference λ between forewing and hindwing decreases and the positional angle θ of hindwing increases, while the θ of forewing remains almost unchanged. The angle between the flapping plane and the axis of the body βbody remains the same during climbs with different η, which causes the angle between the flapping plane and the horizontal plane βH to change between LAC and SAC. Through numerical simulation of LAC and SAC, it can be found that compared with LAC, the direction of the net force relative to the horizontal plane during SAC decreases from 67°to 22°, which is significantly affected by the decrease of βH.